Sub-categorization of Pediatric Small Round Blue Cell Tumors using Immunohistochemistry - Muhammad Mudassar, Shireen Hamid, Muhammad Sarwar Zia, Sadia Hameed, Muhammad Usman, Muhammad Asif Aleem (Journal of Rawalpindi Medical College, 2022)
Introduction: The category of Small Round Blue Cell Tumors includes neoplasms that are undifferentiated and contain similar-looking growth of small round blue cells having bigger nuclear size as compared to the cytoplasm (high N/C). It includes Non-Hodgkins Lymphoma, Synovial Sarcoma, Ewings Sarcoma/ Primitive Neuroectodermal Tumor, Rhabdomyosarcoma, Hepatoblastoma, Retinoblastoma, Neuroblastoma, Neuroendocrine carcinoma, Nasopharyngeal Carcinoma, Desmoplastic Small Round Cell Tumor, Dysgerminoma, and Wilm’s tumor. Immunohistochemistry can be very helpful in the accurate diagnosis of this diverse group of tumors. Objective: The objective of the study is to sub-categorize pediatric malignant small round blue cell tumors using immunohistochemistry. Study design: Descriptive cross-sectional study Setting: Meezan private lab, Faisalabad, Pakistan Duration of study: 4 years, from January 2017 to December 2020. Sample size: 46 cases. Sampling technique: Non-probability purposive sampling Materials and Methods: 46 cases, which fulfilled the inclusion and exclusion criteria were selected for the study. All these cases were subjected to immunohistochemistry. The IHC technique used was based on the Peroxidase anti-peroxidase (PAP) method. Based on site and morphological clues, initially Leukocyte common antigen (LCA), Myogenin, Cytokeratin (CK), Desmin, Chromogranin, Neuron Specific Enolase (NSE), S-100, Smooth Muscle Actin (SMA), and CD99 were used. Further immune stains panels were used afterward, as and when needed like CD20, CD3, CD30, BCL2, CD117, Ki-67, Tdt, Synaptophysin, SMA, CD56, Melan A, HMB45, and WT1. Results: Among all the malignant Small Round Cell Tumors, Rhabdomyosarcoma was the highest in frequency i.e. 8 (17.4%), followed by Ewing’s sarcoma/PNET 7(15.2%). Both Diffuse Large B cell lymphoma and Neuroblastoma were 5 each in number (10.9%). Non-Hodgkins lymphoma as a whole was 13 (28.2%), including 5 cases (10.9%) of diffuse large B cell lymphoma, 4 cases (8.7%) of T lymphoblastic lymphoma, 3 cases (6.5%) of Burkitt’s lymphoma, and only 1 case (2.2%) of NK/T cell lymphoma. Conclusion: Immunohistochemistry is an essential tool for accurate sub-categorization of pediatric small round blue cell tumors.